Pan-nationalism and the European Union: how to achieve a European political and cultural identity - Angelina Banović-Markovska (Kultura (Skopje), 2014)
Acceptance of the European Union as the common perspective of the various nationalities, does not necessarily exclude ethnicity; on the contrary, it is an effort that may see implemented a rational and political construct that aims to preserve uniqueness. As dictated by the Universalist concept of the union, peculiarities are crucial in forging the long awaited common European cultural identity, as a socio-psychological pendant of the national identities.